Readiness for autonomous English language learning: The case of Indonesian undergraduate students - Daflizar, Daflizar; Petraki, Eleni (Indonesian Journal of Applied Linguistics, 2022)
The purpose of this study was threefold: (1) to investigate how Indonesian undergraduate students perceive their teachers’ and their responsibilities in English language learning; (2) to investigate how the students perceive their abilities related to autonomous English language learning; (3) to examine if there are differences in the students’ perceptions of their responsibilities and abilities concerning gender and majors of study. The study employed a mixed-methods research approach with a sequential explanatory design and recruited 402 participants in the quantitative phase and 30 participants in the qualitative phase. The data were collected through questionnaires and semi-structured interviews. The findings showed that the majority of students deemed the teacher to be the one in charge of their learning despite their positive perceptions of their abilities. No significant difference was found between males and females in their perceptions of responsibilities and abilities. Regarding majors of study, no significant difference was found between English major students and non-English majors in their perceptions of their abilities; however, there was a significant difference between the groups’ perceptions of their responsibilities. The research advocates the need for awareness-raising on the benefits of learner autonomy and appropriate teacher training for the Indonesian context.